Pengaruh Keterikatan Kerja dan Motivasi Kerja terhadap Kinerja Pegawai pada Kantor Pengujian Kendaraan Bermotor Wiyung Dinas Perhubungan Kota Surabaya - Nugroho, Prasetyo Widi (Seminar Nasional Manajemen, 2025)
This study aims to analyze the partial effect of work engagement and work motivation on employee performance at the Motor Vehicle Testing Office of Wiyung, Department of Transportation, Surabaya City. A quantitative approach with an explanatory method was employed. The population consisted of 62 active employees, and total sampling was applied. Data were collected through a closed-ended questionnaire using a Likert scale, and analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results show that both work engagement and work motivation have a significant positive effect on employee performance. Work engagement is reflected in enthusiasm, dedication, and emotional involvement, while work motivation represents internal and external drives to complete tasks optimally. Together, these variables significantly contribute to improving employee performance. These findings provide a strategic basis for human resource management in the public sector.